A SYNTACTIC ANALYSIS OF THE DRAMA SCRIPT” BEAUTY IS A BEAST BY D. M. LARSON - Hasby, Muhammad Asrul (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The research aimed to know students’ sentences of the script are analyzed by the syntactic rule that is limited to the verb sentences, parts of speech, phrases, and constituency by employing syntactic distribution and tree structure. The research used descriptive qualitative research. The technique of collecting data used a sheet of the script by taking a number of verb sentences and the data was analyzed by used qualitatively. Based on the result of data analysis, there were four points of syntactic structure found in the sentences of the script namely: 1). Overt Constituents that characterized all phrases and clauses have an overt form, 2) Empty Constituents that characterized a null projection form in some phrases or clauses and divided into four types known as Covert Complements, Empty complemented, Empty T Constituent and Empty Subject of Infinitive. 3). There were several sentences in the script indicating syntactic disorder as specifically known as Agrammatism which is syntactically less complex than the target reconstructions in omissions and simplifications typically affect functional projections (DP, TP, and CP). 4). In addition, a sentence was not based on syntactic distribution that occupied a VP after Determiner.